Molecular Detection of Medically Important Carbapenemases Genes Expressed by Metallo-Î²-lactamase Producer Isolates of Pseudomonas aeruginosa and Klebsiella pneumoniae - Al-Ouqaili, Dr. Mushtak T. S. (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objectives: The increase in antibiotic resistance among Pseudomonas aeruginosa and Klebsiella pneumoniae especially through the production of metallo-Î²-lactamases (MBLs) puts the use of the carbapenems for therapeutic purposes at risk. The study aimed for preliminary screening and phenotypic confirmatory tests for the production of MBLs. Further, to investigate the role of blaVIM, blaNDM, and blaIMP in addition to blaOXA-48 and blaKPC, respectively, in the resistance to carbapenems. Furthermore, to detect gene expression represented coproduction of the assigned enzymes encoding genes using real-time polymerase chain reaction (RT-PCR). Patients and Methods: A total of 100 specimens had been taken from 92 patients. All of these specimens were examined by microbiological culture technique. Both double disk synergy (DDS) and combined disk (CD) techniques were used as a confirmatory test for MBL production. Gene expression for Class A, B, and D MBLs was detected by RT-PCR. Results: Out of 34 potential MBLs producer clinical isolates of P. aeruginosa and K. pneumonia, 21 (62.0%) and 6 (18.0%) were positive for DDS test, respectively. All isolates (100%) of the potential MBLs producer isolates of P. aeruginosa and K. pneumonia were positive for the presence of meropenem alone plus meropenem-EDTA. Molecular assay revealed that a total of 26 (96.0%) of P. aeruginosa were confirmed as blaOXA-48 producer isolates. Further, out of27 MBL positive P. aeruginosa, 25 (93.0%) were confirmed as blaVIM producer isolates. Further, all isolates of K. pneumonia (100%) were confirmed as blaVIM but no gene expression observed for blaIMP P and blaKPC C against P. aeruginosa and K. pneumonia. Further, our study result yielded that out of 27 P. aeruginosa positive isolates for MBL, 21 (78.0%) were confirmed as blaNDM producer isolates. Furthermore, our study result revealed that out of 7 pneumonia positive isolates for MBL, 6 (86.0%) were confirmed as blaVIM producer isolates. Coproduction of blaVIM and blaOXA-48 encoding genes was produced by all study isolates of K. pneumoniae. Conclusion: CD test is more preferred than double-disk synergy test for phenotypic confirmatory test for checking carbapenemases production. Further, blaVIM, blaNDM, and blaOXA-48 carbapenemases play an important role in resistant to carbapenems represented by imipenem and meropenem among study isolates of P. aeruginosa and K. pneumonia using RT-PCR. Coproduction of blaVIM and blaOXA-48 encoding genes was detected in all study isolates of K. pneumonia. The expression of blaVIM, blaOXA-48, and blaNDM genes in the study isolates at high proportion by K. pneumonia. blaOXA-48 could be the reason why these isolates were endemic in Iraqi patients.